The Educational Strategy of Pesantren through OSDAP (Darussalam Parmeraan Santri Organization) in Anticipating Bullying Among Santri: Strategies for Prevention and Intervention - Mgr Sinomba Rambe; Faizah Nur Atika; Ismail Syakban; Muhammad Nizar Al Bashir; Al Jihadul Haq; Ahmad Rizki (Ta’dib : Jurnal Pendidikan Islam, 2025)
The escalation of bullying in educational settings poses a serious threat to students’ character development. This study aims to analyze anti-bullying prevention and intervention strategies implemented at Pondok Pesantren Darussalam Parmeraan through the Darussalam Parmeraan Student Organization (OSDAP). Using a qualitative case study approach, data were collected through observation, interviews, and document analysis. The findings reveal that OSDAP functions as an effective institutional agent in fostering anti-bullying awareness by organizing structured student forums that encourage empathy, emotional expression, and peer solidarity. These efforts are strengthened by firm pesantren regulations with educational sanctions and the systematic internalization of Islamic values—particularly compassion, tolerance, and respect—across academic, extracurricular, and mosque-based activities. This study demonstrates that anti-bullying education in pesantren operates as an integral component of holistic Islamic character education rather than as an isolated disciplinary measure. The integration of moral instruction, organizational involvement, and religious practices contributes to the creation of a safe educational environment and the development of students’ social responsibility and moral resilience.